(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
This paper analyzes the holding of municipal elections in Peru in the context of the civil war that pitted the provisional liberal government of General Ramón Castilla against the conservative rebel army of General Manuel Ignacio de Vivanco between November 1856 and March 1858. I argue that these elections were not directly affected by the war, but were occasionally conditioned by a “civil war” discourse. This rhetoric when activated came to question the functioning of municipalities, as was the case of the municipality of the city of Lima accused of conspiracy.